Study of the Nanocomposite Mo2C(1-x)-TiC(x)-SWCNTs by Field Actived Sparck Plasma Sintering Process - Bendjemil, Badis; G. Noudem, Jacques; Mouyane, Mohamed; Bernard, Jérôme; Guhel, Yannick; Houivet, David (Journal of Advances in Nanotechnology, 2020)
Nanocomposites are worn resistant materials used in cutting tool applications. The materials are composed of ultrafine powder hard phase grains surrounded by a tough binder phase carbon nanotubes (Mo2C)1-x–(TiC)x (2≤x≤4)//1Wt% SWCNTs. Composite bicarbide Mo2C-TiC was rapidly synthesised and simultaneously consolidated by field activated sintering technique (spark plasma sintering) at which the extensive volume expansion occurred as a function of the volumic fraction from 20 to 40 vol.% of TiC powders and 1 Wt.% of SWCNTs was reinforcement of the NCMC’s. The sintered powder mixture was examined by XRD patterns, the morphology of the obtained phase was observed by SEM and the phase compositions in different regions were analyzed by EDX. The composites were processed using Field Activated Sintering Technique, spark plasma sintering (SPS) at temperatures in the range of 1700-1800°C with addicting of SWCNTs. The effects of SWCNTs addition on phases morphology, microstructure hardness and fracture toughness of the nanocomposite were investigated. The best product contained 1.0 Wt% SWCNTs from (Mo2C)1-x–(TiC)x , x= 0.2 which was sintered at 1700°C, 70 MPa for 10 min, M0.8T0.2/ 1 Wt% SWCNTs exhibit a better density, highest hardness and good ductility. Relative densification was achieved 99.5 % from the theoretical and good mechanical properties like hardness and fracture toughness (KIC=5.6 Mpa m1/2) are improved. The results were confirmed using Raman scattering resonant spectroscopy.
Keywords: SWCNTs; FASTSPS; Shrinkage; Microhardness; Fracture Toughness.; Raman Spectroscopy.